The paradox of living law positivization in the new criminal code: a critique of legal formalism - Teuku Muttaqin Mansur; Erwin Soesilo (Jurnal Geuthèë: Penelitian Multidisiplin, 2026)
The recognition of living law in the New Criminal Code (NCC) indicates a shift toward legal pluralism, but it also raises serious conceptual and practical issues. However, there is still a lack of research specifically examining the gap between the recognition of living law in the NCC and its application when confronted with the principle of legality. This study aims to examine the conflict between the principle of legality and the effort to positivize living law through regional regulations that risk eliminating its organic and contextual nature. This research uses a normative juridical method, drawing on statute, legal philosophy, and socio-legal conceptualization, through an analysis of the regulation of living law in the NCC and Eugen Ehrlich's thoughts on living law in society and the principle of legality. The research results show that the positivization model in the NCC actually transforms living law into rigid written norms, thereby reducing its dynamic character and turning it into little more than a symbol of legitimacy in court decisions. This research also found that this formalization reproduces the logic of colonial law, which places state law above the social realities of society. As a reconstruction, this research proposes integrating living law through judicial discretion and legal discovery mechanisms, rather than through rigid formal codification that restricts living law itself. In conclusion, living law can only function fairly if it is maintained as organic law by strengthening the role of judges and customary institutions within the criminal justice system and customary courts.